1986
DOI: 10.1128/iai.54.3.774-779.1986
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic characterization of the P6 protein of nontypable Haemophilus influenzae

Abstract: The purpose of this study was to characterize the degree of antigenic heterogeneity or conservation of a 16,600-dalton outer membrane protein (P6) among strains of nontypable Haemophilus influenzae. Immunization of rabbits with P6 isolated from individual strains resulted in antibody to P6 of all 25 strains tested. The titers of antibody in the sera were similar among the strains. Whole organisms of two strains were used to immunize rabbits, and antibodies were produced to P6 of all strains tested. Monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 19 publications
3
74
0
Order By: Relevance
“…They employed shearing of whole cells to remove the OMs. Baeteroides intermedius OMs possessed a 20 kD protein similar to the ompH protein of Pseudomottas aertigitiosa (26), and Haemophihis ittfhiertzctc (31). High molecular weight (120 to 130 kD) OMPs were also observed in these B. intermedius OMs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They employed shearing of whole cells to remove the OMs. Baeteroides intermedius OMs possessed a 20 kD protein similar to the ompH protein of Pseudomottas aertigitiosa (26), and Haemophihis ittfhiertzctc (31). High molecular weight (120 to 130 kD) OMPs were also observed in these B. intermedius OMs.…”
Section: Discussionmentioning
confidence: 92%
“…4, Lane 2). A total of 10 MOMPs were observed after heating at 65''C with relative molecular weights of 46,42,37,35,31,30,27,24,20, and 18 kD. At lOO^C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that even stnall amounts of these proteins (24 and 16.5 kDa) were sufficient to produce a strong immunologie reaction, and that the 24 kDa protein seemed to be a particularly potent antigen. It is interesting that a 16.6 kDa OMP, referred to as P6, has been identified so far in all examined strains of Haemophilus itrflttenzae (14), an important pathogen in both adults and ehildren. P6, being a target for baeterieidal antibodies, may be an itnportant surfaee antigen with regard to host immunity and vaccine development towards this organistn.…”
Section: Discussionmentioning
confidence: 99%
“…They have many important functions, serving as phage receptors (6), diffusion pores, proteases, mitogens (7) or taking part in conjugation (26). Due to their itntnunogenicity sotne OMP may be possible candidates for itnmunotherapy (3,14). Although sotne attention has been paid to OMP of some strains of A. aeiinomyeeiemeomiians and H. aphrophiltis (8), mostly protein profiles of whole bacterial cell extracts have been studied (29).…”
mentioning
confidence: 99%
“…The 40-kDa protein of F. nucleatum shares sequences with the OmpA protein of Escherichia coli [5]. Brucella abortus strains share antigens among OMPs of porin nature that appear to be species wide [30] and in Haernophilus influenzae an OMP antigen has been shown to be antigenically preserved among strains [31].…”
Section: -6-mentioning
confidence: 99%